Effectiveness of First Aid Training in Improving Emergency Response Competence among High School Students: A Community Service Study (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This study evaluates a community service program aimed at improving high school students’ competence in first aid management during emergency situations. A pre-experimental one-group pretest–posttest design was applied to 30 students at YPSIM School. The intervention included lectures, audiovisual media, and hands-on practice. Data were collected using a 10-item questionnaire administered before and after the training. The results indicate a significant improvement in knowledge, with mean scores increasing from 61 to 90. The combination of instructional methods proved effective in enhancing students’ understanding and practical skills. However, certain topics, particularly symptoms of menstrual pain, require further reinforcement. This program contributes to strengthening students’ preparedness and promoting a safer school environment.